¿Contribuyen los programas de prevención y tratamiento de la hipertensión arterial al control de la enfermedad? (2008)
ABSTRACT: Hypertension is a progressive disease that remains as an asymptomatic disease for a long period of time, causing damage on specific organs like heart, kidney, and blood vessels; for that reason prevention and educational health programs should be implemented. Objective: To analyze, the view that patients have about health service’s hypertension programs that help patients to control and prevent the disease risk factors. Materials and methods: Descriptive cross sectional study; the sample was selected in a not probabilistic approach from the participating health services. Results: 52% of the patients perceived that drinking alcohol decreased due to the recommendations given in the program, and also 42 % that were active smokers at the moment of the interview, 26 % quit smoking with those recommendations. 74 % of participants do exercises then 65% told to start work out when they were involved in the program. About food intake 92% of the Participants reported reduction in fat intake, 91% in salt consumption and 86 % decrease salt addition to food. Conclusions: Health education activities given to patients help them to take part in their control and prevention of hypertension disease.